Autopsy Findings and Histopathological Corroboration in A Case of Death due to Hornet Bite - Chowdhuri, Soumeek; Chatterjee, Biswajit; Sapui, Samiran; Das, Aniruddha; Biswas, Saswata; Mukhopadhayay , Parthapratim (Journal of Indian Academy of Forensic Medicine, 2015)
We present a rare case of death due to hornet bite in an adult 64 years old patient who died within 6 hours of admission. There were bites on multiple sites and histopathology of Kidney showed acute tubular necrosis. Liver shows fatty changes periportal fibrosis and portal inflammation. Lungs show intra-alveolar exudation, alveolar wall destruction and inflammatory infiltrates. Heart showed deposition of lipofuschin and brain showed focal oedema with dilatation of vessels. These accidents can occur in places of cohabitation of hornets with humans. People who are allergic to wasp venom are also allergic to hornet stings. In severe cases, allergic individuals may go into anaphylactic shock and die unless treated promptly. Clinical criteria for fatal cases can be formulated from this case and especially susceptible individuals like elderly with co morbid conditions and children should be treated early and extensively to avoid fatal complications.